Perspektif Manajemen Syariah Melalui Kepemimpinan dan Pengelolaan Aset Dalam Meningkatkan Kinerja Perusahaan di Kebun Klambir Lima Kabupaten Deli Serdang - Wilchan Robain; Harianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sharia Management Perspective Through Leadership and Asset Management in Improving Company Performance in Klambir Lima Deli Serdang Gardens. The formulation of the research problem is how is the perspective of sharia management through leadership and asset management in improving company performance. This study aims to determine how the influence of sharia management and leadership perspectives on asset management and how the influence of sharia management and leadership perspectives on company performance. Data analysis in this study used path analysis assisted by the SPSS 16 for Windows computer program. The results of the study show that the variable perspective of sharia management and leadership simultaneously has a positive and significant effect on asset management in Kebun Klambir Lima, Deli Serdang Regency. perspective of sharia management and leadership partially and simultaneously has a positive and significant effect on company performance in Klambir Lima Plantation, Deli Serdang Regency